Optical based relative humidity sensor using tapered optical fiber coated with graphene oxide - Mohamed, Habibah (AIP CONFERENCE PROCEEDINGS, 2016)
A tapered silica optical fiber (SOF) coated with graphene oxide is proposed and demonstrated as a humidity sensor. In order to reduce the diameter of the optical fiber from 125 µm to 26.9 µm as the sensing region, the flame-brushing technique was used to taper the fiber with the tapering length is about 30 mm. To increase the optical sensitivity, the tapered region was coated with graphene oxide, which will interact with the changes of humidity and affect the evanescent field in the tapered region. In this work, the proposed optical sensor works in the range of the humidity from 40% to 60%. The comparison was made between uncoated tapered fiber with the graphene oxide coated optical fiber and the experimental works reveal that the tapered fiber coated with graphene oxide gave better result compared to bare tapered optical fiber. It is showed that the tapered SOF with graphene oxide enables to increase the sensitiveness of the fiber to sense relative humidity.